Activated nitrogen doped graphene shell towards electrochemical oxygen reduction reaction by its encapsulation on Au nanoparticle (Au@N-Gr) in water-in-oil ``nanoreactors'' - Dhavale, Vishal M.; Gaikwad, Sachin S.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2014)
Encapsulation of nitrogen doped graphene on Au nanoparticle (Au@N-Gr) could be accomplished through a water-in-oil emulsion technique, where the emulsion droplets act as `nanoreactors' and the redox reaction inside the droplets results in the formation of core-shell nanoparticles. The encapsulation of N-Gr on a small quantity of Au (N-Gr : Au wt ratio of 90 : 10) made the N-Gr layer more conductive and active towards electrochemical oxygen reduction reaction (ORR). The enhanced conductivity helped the system narrow down the ohmic overpotential, and direct electronic interactions between the Au and Gr layers brought in a favourable positive shift to the onset potential for ORR. Encapsulation has helped N-Gr reduce the overpotential by similar to 121 mV as compared to N-Gr alone. Apart from this, the oxygen reduction kinetics of Au@N-Gr also appeared to be superior to N-Gr and Au nanoparticles as separate entities due to greater involvement of the preferred 4-electron reduction pathway. At -0.3 V (vs. Hg/HgO), the percentage of hydrogen peroxide (H2O2) (a product formed from the undesirable 2-electron reduction pathway) was found to be 16.5% for Au@Gr, where Au was covered with undoped Gr, which gets reduced to a significantly low level of 6.5% for Au@N-Gr. Au and N-Gr as separate entities give yield of H2O2 as 52.2 and 47.7%, respectively. From these, it can be concluded that the coverage of N-Gr on Au helps decrease the yield of H2O2 drastically apart from the benefits of synergistic interactions in reducing both ohmic and activation overpotentials.